2003
DOI: 10.1291/hypres.26.807
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-Ankle Pulse Wave Velocity Is Useful for Evaluation of Complications in Type 2 Diabetic Patients

Abstract: Pulse wave velocity (PWV) is useful for the evaluation of aortic stiffness. The brachial-ankle PWV (baPWV)and carotid PWV (from heart to carotid) were compared to study the relation of these two types of PWVs to diabetic complications in patients with type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 17 publications
2
63
1
1
Order By: Relevance
“…Aso et al also demonstrated that baPWV is closely related to diabetic retinopathy 20) ; however, our study produced conflicting results. As mentioned earlier, different patient baseline characteristics and methods to measure arterial stiffness may have caused this discrepancy.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Aso et al also demonstrated that baPWV is closely related to diabetic retinopathy 20) ; however, our study produced conflicting results. As mentioned earlier, different patient baseline characteristics and methods to measure arterial stiffness may have caused this discrepancy.…”
Section: Discussioncontrasting
confidence: 70%
“…Few previous studies 7, [16][17][18][19][20] have investigated the relationships between diabetic microvascular complications and arterial stiffness, as assessed by the carotid-femoral PWV (cfPWV). One study reported that the presence of microalbuminuria is correlated to arterial stiffness only if BP variables are excluded from multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we also found that serum IL-18 levels were positively correlated with carotid IMT and baPWV in patients with type 2 diabetes. Several studies have reported that carotid IMT (11,12) and baPWV (31) are useful markers for evaluation of atherosclerosis in type 2 diabetes. A clinical study reported that decrease in glomerular filtration rate is linked to atherosclerosis (32).…”
Section: Il-18 Is a Predictor Of Diabetic Nephropathymentioning
confidence: 99%
“…To estimate the effect of increasing steps/day during the study, ∆steps/day was calculated using the following formula 20) : ∆steps/day = ∑{(steps/day at Week X) -(steps/day at Week 0)} *(X=1- 16) To evaluate change in baPWV, we set a cut-off baPWV = 1,700 cm/s. Although there is no clear cut-off value of baPWV that defines organ disorders 21) , this value is a predictor of several health disorders such as all mortality 22) , type 2 diabetes mellitus 23) , cerebral ischemic small vessel disease 24) and acute coronary syndrome 25) . Each subject was categorized as either 'high' or 'low' according to his or her starting baPWV above or below the cut-off value.…”
Section: Discussionmentioning
confidence: 99%